Incidence of Sacralization of 5th Lumbar and First Coccygeal Vertebrae: An Osteological Study on Dried Sacra of Pakistani Population (Journal of Fatima Jinnah Medical University, 2024)
Background: Sacralization can occur when the fifth lumbar or the first coccygeal vertebra fuses with the sacrum. Given the increasing incidence of lower back pain and its impact on human health and wellbeing, understanding the etiology of sacralization is important. The study aimed to estimate the incidence of sacralization of the fifth lumbar and first coccygeal vertebrae in the sacrum and to define the types of sacralization observed in the cadaveric sacra.Methods: A descriptive study was done on 285 adult human dry sacra from bone bank of Fatima Jinnah Medical University and Rashid Latif Medical College in Lahore, Pakistan. The study involved examining the number of vertebral segments and sacral foramina and classifying the sacra into different types. We also calculated the sacral index and measured the length and width of these sacra.Result: Out of the sample, 68% of sacra were typical, while sacralization was observed in 32% of cases. Among the sacralized sacra, 70 % were fused with the fifth lumbar vertebra (L5) and 30% were fused with the first coccygeal vertebra. The incidence of sacralization was similar in both genders.Conclusion: Sacralization is common and can be asymptomatic or associated with low back pain, disc degeneration/ herniation, scoliosis, and spondylolisthesis. Surgeons, anesthetists, obstetricians, and physicians can benefit from this knowledge to treat a wide range of patients.
Keywords: Sacrum; Coccyx; Low back pain; Disc Herniation